2018
DOI: 10.3390/su10061904
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Stock Market Participation via Technologies: The Role of Households’ Risk Attitude and Cognitive Ability

Abstract: This article reviews the relation between social capital and stock market participation via new technology. Its purpose is to acquire a thorough understanding of the structural, relational, and cognitive aspects of social capital's influences and to recommend further empirical research ideas to the existing body of knowledge on household finance. It discusses the consideration of modern and highly technological platforms such as the internet stock market exchange platforms and applications. The stock market pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Further, risk attitudes have partially mediated the relationship between money attitudes and stock market participation as supported by Cheng et al (2018) and Saurabh and Nandan (2018). These results support the previous studies findings (Wood and Zaichkowsky, 2004) and indicate that the investors who are risk-seekers increasingly participate in the stock market as supported by Cheng et al (2018) and Akhtar and Das (2019). It indicates that the investors who are risk-seekers tend to invest in stocks rather than bonds and those investors who play it safe increasingly invest in bonds as compared to stocks as supported by Keller and Siegrist (2006b).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Further, risk attitudes have partially mediated the relationship between money attitudes and stock market participation as supported by Cheng et al (2018) and Saurabh and Nandan (2018). These results support the previous studies findings (Wood and Zaichkowsky, 2004) and indicate that the investors who are risk-seekers increasingly participate in the stock market as supported by Cheng et al (2018) and Akhtar and Das (2019). It indicates that the investors who are risk-seekers tend to invest in stocks rather than bonds and those investors who play it safe increasingly invest in bonds as compared to stocks as supported by Keller and Siegrist (2006b).…”
Section: Discussionmentioning
confidence: 94%
“…It has also been investigated that less risk aversion predicts participation in various models (Haliassos and Bertaut, 1995). Further, risk attitudes mediate the relationship between social capital and stock market participation (Cheng et al, 2018). Saurabh and Nandan (2018) have confirmed the mediating role of risk attitudes toward financial satisfaction.…”
Section: Risk Attitudes and Stock Market Participationmentioning
confidence: 88%
See 2 more Smart Citations
“…Sustainable finance is strongly linked to financial sustainability, which is related to structural, relational and cognitive aspects that create value for a company [4] and the long-time survival capacity of companies. The link between business sustainability and the financial performance of a firm has been demonstrated by several studies, as reference [5] showed.…”
Section: Introductionmentioning
confidence: 99%